The humanistic viewpoint - Jakobsson, Olof (My University, 2020)
Interest in STEM-subjects is declining. One proposed solution would be to apply a more humanistic approach to teaching, Vision II, instead of the canonical approach, Vision I. This study reviews the current stand on Vision II in science education and examines one way of introducing Vision II to a group of students with streamlined technical backgrounds, enrolled in a master program which gives both an engineering and a teaching degree, how they perceive it and why they think it should be applied. Using a phenomenographic analysis their perceptions of Vision II are categorized and hierarchically sorted in an outcome space. The results show that students’ perceptions in regard of the “how”-question can be sort in a matrix with axis corresponding to different levels of autonomy and concretization. The answers to the “why”-question can be sorted in an outcome space with an increased level of complexity corresponding to the two categories “Literacy” and “Utility” and a low level of complexity corresponding to the category “Interest/Relevance”. The study is concluded with a short discussion on the need for humanities in swedish high school science and technology education.
Keywords: Vision II; humanistic; phenomenograpy; learning